Seed dispersal by reintroduced woolly monkeys suggest that plant traits are more important than learning (2021)
Woolly monkeys (Lagothrix lagothricha) are endangered because of habitat destruction, hunting, and illegal trade, which leads to captive individuals. As survival and reproductive rates are low in enclosures, reintroduction has been considered as a conservation strategy that allows the reestablishment of populations and the restoration of ecological functions, such as seed dispersal. In this study, we report seed dispersal by a group of reintroduced woolly monkeys, and determine the factors associated with this process. We assessed the hypothesis that seed dispersal depends on inherent factors of their interaction with plants (i.e. pulp-seed attachment and diaspore size), and we also examined whether seed dispersal depends on a learning process. In this study, we reintroduced nine individuals, but we obtained data just for four survivors at the Rey Zamuro Natural Reserve, Meta (Colombia). We found that pulp-seed attachment was the most important variable explaining the chance of seed dispersal, as plants with pulp...